ANALYSIS OF SERVICE QUALITY USING SERVICE QUALITY (SERVQUAL) AND SWOT METHOD IN BORDER AREA (CASE STUDY: PT. JABABEKA MOROTAI) - Amrin Sibua; Almukmin Umar; Wahyu Sibua; Dandi Weka (Center for Study and Journal Management FTI UMI, 2022)
Pavilliun d'loha Resot Jababeka Morotai or commonly called PT. Jababeka Morotai which is managed by Jababeka group which is a company in the management of the first open industrial estate in Indonesia which is listed on the Jakarta and Surabaya stock exchanges since 1994. where the three main pillars in this company are land development, infrastructure, and entertainment venues and hospitality. PT. Jababeka Morotai so far, has never measured the level of visitor satisfaction in the hospitality field with Hotel Guests so that in improving the quality of service and also in overcoming complaints of hotel guests, it is still not carried out properly. Based on the above problems, this study uses the SERVQUAL method and SWOT analysis (strength, weakness, opportunities, Threat). The SERVQUAL method is a method used to find out the extent of differences in reality and expectations for the services received / felt by customers, SWOT is a way to systematically identify various factors in order to formulate a company strategy. The result of the study is the quality of service of the five dimensions of SERVQUAL, the perception value is 4.61 and the Expectation value is 4.32 with a positive gap value (0.28) so that it is considered good because it is in accordance with the level of expectations of consumers or guests. From SWOT, strategies are obtained which maintain prices, increase promotions, advertising, brochures and social media.